Estimating daily evapotranspiration from remotely sensed instantaneous observations with surface flux equilibrium (SFE) theory and maximum entropy production (MEP) principle - Xin Pan; Zhanchuan Wang; Jinlong Shi; Yuanbo Liu; Zi Yang; Xu Ding; Suyi Liu; Hongjun Zhu; Congbao Zhu; Shile Yang; Yingbao Yang (Journal of Hydrology, 2026)

Associations of prenatal PFAS exposure with offspring neurobehavioral outcomes by maternal folate supplementation and cord blood 5-MTHF levels: a prospective birth cohort study - Susu Wang; Chunping Hu; Xin Liang; Lijun He; Hongjun Shi; Shuhua Yang; Ji Bian; Qianlong Zhang; Junjie Ao; Fei Li (Environmental Research, 2026)

Form-dependent chloroform adsorption behavior from powdered to sintered carbon - Qing Gao; Zhilong He; Jianjun Cheng; Jingwen Li; Dapeng Zhou; Jiahua Shi; Xiuli Chen; Hongjun Liu (Journal of Environmental Chemical Engineering, 2026)

Soil organic carbon and pH govern the divergent trajectories of organic and inorganic sulfur under long-term fertilization - Haotian Shi; Miao Lei; Shaomin Huang; Hongjun Gao; Lu Zhang; Dongchu Li; Shulan Zhang; Xianlu Yue; Qingxu Ma; Wenju Zhang (Journal of Cleaner Production, 2026)

Mitigating PM2.5 exposure and health impacts for school-aged children: The role of street canyon layouts and greenery design - Chen Ren; Chang Xi; Yaru Meng; Hongjun Zhang; Mingming Zhao; Shi-Jie Cao (Urban Climate, 2026)

Particle size–dependent molecular perturbations induced by copper nanoparticles in marine medaka (Oryzias melastigma): an integrated miRNA–mRNA analysis - Pengrui Ren; Peipei Zhang; Jingyuan Shi; Hongbo Li; Ruofei Jin; Hongjun Li (Frontiers in Marine Science, 2026)
Introduction Copper nanoparticles (Cu-NPs) have been increasingly released into marine environments due to their extensive applications, posing potential risks to marine organisms and human health. Although Cu-NPs of different particle sizes exhibit distinct toxicities—largely attributed to variations in specific surface area and Cu 2+ dissolution rates—current physicochemical parameters still fail to fully explain these toxic effects, and the underlying molecular mechanisms remain unclear. Methods This study aimed to investigate the toxic effects and underlying molecular mechanisms of Cu-NPs of different nominal primary diameters (10 nm, 50 nm, and 100 nm) on the marine medaka ( Oryzias melastigma ). Results LC 50 point estimates suggested slightly higher toxicity for smaller Cu-NPs. Integrated miRNAomic and transcriptomic analyses revealed that Cu-NPs-10 exposure markedly activated multiple metabolic pathways, including drug metabolism–cytochrome P450, retinol metabolism, and ascorbate and aldarate metabolism. Cu-NPs-50 exposure primarily affected neurodevelopment and synaptic signaling, with predicted miRNA–mRNA associations including miR-202 with mprip-like and miR-2187 with adgrg2-like . In contrast, Cu-NPs-100 exposure activated inflammation- and barrier repair-related networks, with potential miRNA–mRNA relationships involving miR-202 with tm4sf5 , miR-106a, miR-132c, miR-200b, and miR-202 with znfx1 , as well as miR-2187 and miR-202 with rhbdl2 . Discussion Collectively, the integrated miRNA–mRNA analysis suggests that smaller Cu-NPs show a correlation with more intense molecular stress responses than larger particles under seawater transformations (e.g., aggregation/dissolution), and provides insights into the key regulatory networks potentially underlying these size-associated responses.

Lacticaseibacillus paracasei subsp. paracasei Q- 1 Exhibits Good Safety and Effectively Prevents Escherichia coli K99-Induced Diarrhea in Mice - Fengjie Wang; Li Chen; Yang Li; Guangping Gao; Yanan Wang; Ruili Shi; Hongjun Zhang; Yingyu Chen; Rui Cao; Qiumei Shi; Tonglei Wu (Probiotics and Antimicrobial Proteins, 2026)

A modified curve number method for runoff prediction of different vegetation types at the slope scale in China - Jinle Yu; Hongjun Chen; Miaomiao Wang; Jiachi Bao; Wenyi Song; Xitong He; Wenhai Shi (Soil and Tillage Research, 2025)

Facile synthesis of high-performance crystalline zirconium phosphate adsorbents and its ammonium ion intercalation mechanism for next-generation hemodialysis - Jingwen Feng; Jianjun Cheng; Jingwen Li; Susu Jia; Feiping Cao; Jiajin Feng; Dapeng Zhou; Jiahua Shi; Choon-Hong Tan; Hongjun Liu (Journal of Environmental Chemical Engineering, 2025)

Soil carbon dioxide dynamics in deep profiles under erosional and depositional conditions on the Chinese Loess Plateau - Jiachi Bao; Tiantian Chen; Wenyi Song; Miaomiao Wang; Hongjun Chen; Jinle Yu; Wenhai Shi (CATENA, 2025)

Heat stroke-induced central nervous system injury: Mechanisms and therapeutic perspectives - Wenjun Yang; Zhen Gao; Chengjin Wang; Min Wang; Yuan Cao; Yun Li; Shaoqing Shi; Yiqi Wu; Lu Wang; Hongjun Kang (Journal of Thermal Biology, 2025)

A modified curve number method for runoff prediction of different soil types in China - Miaomiao Wang; Yangdong Zhao; Wenhai Shi; Jinle Yu; Tiantian Chen; Jiachi Bao; Wenyi Song; Hongjun Chen (CATENA, 2025)

A comprehensive OBD data analysis framework: Identification and factor analysis of high-emission heavy-duty vehicles - Zeping Cao; Kai Shi; Hao Qin; Zhou Xu; Xiaoyang Zhao; Jiawei Yin; Zhenyu Jia; Yanjie Zhang; Hailiang Liu; Qijun Zhang; Hongjun Mao (Environmental Pollution, 2025)

An improved curve number for runoff prediction under different vegetation pattern at slope scale in China - Wenhai Shi; Miaomiao Wang; Jiachi Bao; Jinle Yu; Tiantian Chen; Wenyi Song; Hongjun Chen (CATENA, 2025)

Nonlinear seismic response analysis of liquefiable sites based on effective stress method - Hongjun He; Hanwen Ji; Yang Shi; Xiaohua Ke; Yu Miao (Computers and Geotechnics, 2024)

Which biofilm reactor is suitable for degradation of 2,4-dimethylphenol, focusing on bacteria, algae, or a combination of bacteria-algae? - Jingxin Shi; Ning Wan; Shuhui Yang; Yuanyuan Yang; Hongjun Han (Journal of Hazardous Materials, 2024)

An energy-based framework for predicting vehicle noise source intensity: From energy consumption to noise - Bin Sun; Haibo Wang; Qijun Zhang; Hanchao Shi; Hongjun Mao (Journal of Environmental Management, 2024)

Flow three-dimensionality of wavy elliptic cylinder: vortex shedding bifurcation - Xiaoyu Shi; Md. Mahbub Alam; Hongjun Zhu; Chunning Ji; Honglei Bai; Mohsen Sharifpur (Ocean Engineering, 2024)

Exploring vehicle-centric strategies for sustainable urban mobility: A theoretical framework for saving energy and reducing noise in transportation - Bin Sun; Haibo Wang; Le Hu; Qijun Zhang; Hanchao Shi; Hongjun Mao (Journal of Environmental Management, 2024)

Biotoxicity dynamic change and key toxic organics identification of coal chemical wastewater along a novel full-scale treatment process - Weiwei Ma; Xiaoqi Zhang; Hongjun Han; Xueqing Shi; Qiaoping Kong; Tong Yu; Fei Zhao (Journal of Environmental Sciences, 2024)

New insights into survival strategies and PCB bioremediation potential of resuscitated strain Achromobacter sp. HR2 under combined stress conditions - Jie Shi; Yingying Yang; Shusheng Zhang; Qihua Lin; Faqian Sun; Hongjun Lin; Chaofeng Shen; Xiaomei Su (Journal of Hazardous Materials, 2024)

Molecular oxygen activation: Innovative techniques for environmental remediation - Lili Zhou; Yuting Liu; Hao Shi; Yurui Qing; Cheng Chen; Liguo Shen; Mingzhu Zhou; Bisheng Li; Hongjun Lin (Water Research, 2024)

Green technology outsourcing for agricultural supply chains with government subsidies - Ligang Shi; Tao Pang; Hongjun Peng; Xin Feng (Journal of Cleaner Production, 2024)

Overview of enhancing biological treatment of coal chemical wastewater: New strategies and future directions - Weiwei Ma; Xiaoqi Zhang; Hongjun Han; Xueqing Shi; Qiaoping Kong; Tong Yu; Fei Zhao (Journal of Environmental Sciences, 2024)

Novel strategy to enhance the biological treatment of coal chemical wastewater by nano-zero valent iron loaded fly ash-based activated carbon assisted activated sludge process - Weiwei Ma; Xiaoqi Zhang; Hongjun Han; Xueqing Shi; Qiaoping Kong; Tong Yu; Fei Zhao (Environmental Science and Pollution Research, 2023)

Dissolved organic matter evolution and straw decomposition rate characterization under different water and fertilizer conditions based on three-dimensional fluorescence spectrum and deep learning - Guang Yang; Hongwei Pan; Hongjun Lei; Wenbin Tong; Lili Shi; Huiru Chen (Journal of Environmental Management, 2023)

Novel mesocellular silica foam supported poly(amidoxime-ethyleneimine) network for fast and highly efficient uranium extraction from seawater - Jiajia Yang; Yun Li; Tian Tian; Haitao Shi; Zia Ahmad; Ningbo Geng; Jing Jin; Yanqiang Huang; Haijun Zhang; Hongjun Fan; Jiping Chen (Chemical Engineering Journal, 2023)

An Innovative Approach to Predicting Scour Depth Around Foundations Under Combined Waves and Currents in Large-Scale Tests Based on Small-Scale Tests - Ruigeng Hu; Hongjun Liu; Yao Lu; Xiuhai Wang; Wei Shi (Journal of Ocean University of China, 2023)

Interactions Between Humic Acid and the Forms and Bioavailability of Copper in Water - Hongwei Pan; Lili Shi; Xin Liu; Hongjun Lei; Guang Yang; Huiru Chen (Water, Air, & Soil Pollution, 2023)

Study of spatialtemporal changes in Chinese forest eco-space and optimization strategies for enhancing carbon sequestration capacity through ecological spatial network theory - Shi Qiu; Minzhe Fang; Qiang Yu; Teng Niu; Hongjun Liu; Fei Wang; Chenglong Xu; Mingsi Ai; Jieyu Zhang (Science of The Total Environment, 2023)

Alkali-catalyzed hydrothermal oxidation treatment of triclosan in soil: Mechanism, degradation pathway and toxicity evaluation - Yushuang Chen; Rui Shi; Hongjun Luo; Rong Zhang; Yafei Hu; Haijiao Xie; Neng-min Zhu (Science of The Total Environment, 2023)

Case study on wastewater treatment technology of coal chemical industry in China - Jingxin Shi; Chunyan Xu; Yuxing Han; Hongjun Han (Critical Reviews in Environmental Science and Technology, 2021)

Biological coupling process for treatment of toxic and refractory compounds in coal gasification wastewater - Jingxin Shi; Yuxing Han; Chunyan Xu; Hongjun Han (Reviews in Environmental Science and Bio/Technology, 2018)

Synthesis, Aggregation Induced Emission and Mechanochromic Luminescence of New β-Diketone Derivatives Bearing Tetraphenylene Moieties - Haijie Shi; Rui Liu; Senqiang Zhu; Qiqi Gong; Hong Shi; Xiaolin Zhu; Hongjun Zhu (Journal of Fluorescence, 2016)

Efficacy and safety of quetiapine extended release monotherapy in bipolar depression: a multi-center, randomized, double-blind, placebo-controlled trial - Huafang Li; Niufan Gu; Hongyan Zhang; Gang Wang; Qingrong Tan; Fude Yang; Yuping Ning; Honggeng Zhang; Zheng Lu; Xiufeng Xu; Jianguo Shi; Chengge Gao; et al. (Psychopharmacology, 2016)

Identification and validation of novel low-tiller number QTL in common wheat - Zhiqiang Wang; Yaxi Liu; Haoran Shi; Hongjun Mo; Fangkun Wu; Yu Lin; Shang Gao; Jirui Wang; Yuming Wei; Chunji Liu; Youliang Zheng (Theoretical and Applied Genetics, 2016)

Synthesis, Luminescent Properties of aza-Boron-Diquinomethene Difluoride Complexes and Their Application for Fluorescent Security Inks - Long Gu; Rui Liu; Hong Shi; Qiang Wang; Guangliang Song; Xiaolin Zhu; Shidong Yuan; Hongjun Zhu (Journal of Fluorescence, 2016)

The Alteration of MiR-222 and Its Target Genes in Nickel-Induced Tumor - Jing Zhang; Yang Zhou; Lin Ma; Shunquan Huang; Ruijin Wang; Rongrong Gao; Youjun Wu; Hongjun Shi; Jun Zhang (Biological Trace Element Research, 2013)

Isolation and Characterization of a Novel Noncoding RNA from Nickel-Induced Lung Cancer - Jing Zhang; Yang Zhou; Youjun Wu; Lin Ma; Yingying Fan; Xuan Kang; Hongjun Shi; Jun Zhang (Biological Trace Element Research, 2012)

Identification of Differentially Expressed Genes in Lung Tissues of Nickel-Exposed Rats Using Suppression Subtractive Hybridization - Jing Zhang; Jun Zhang; Yingying Fan; Lihong Liu; Mengjie Li; Yang Zhou; Zhihua Shao; Hongjun Shi; Ying Wang (Biological Trace Element Research, 2011)

Development of combined biological technology for treatment of high-strength organic wastewater and results of case studies - Nanqi Ren; Aijie Wang; Hongjun Han; Fang Ma; Jie Ding; Yue Shi; Dan Zhao (Journal of Ocean University of China, 2006)